Suspek dermatofitosis pada ayam Sentul Debu di peternakan ayam di Kabupaten Majalengka, Jawa Barat - Zega, Defornatasya Indah Sinta Nadania; Hermawan, Firda Aisyah; Triyatjaya, Yoga; Khairani, Shafia; Pratiwi, Unita (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2024)
Dermatophytosis in chickens or avian ringworms is a zoonotic disease caused by fungi in the Dermatophyta group. This article reports a case of suspected dermatophytosis in Sentul Debu chickens on a chicken farm in Majalengka Regency, West Java. Three 11 month old male Sentul Debu chickens in one of the postal system rearing cages showed clinical symptoms in the form of white scales on their head, comb, and wattles. Diagnosis and treatment are based on clinical symptoms and visible lesions. Treatment uses an ointment with the active ingredient sulfur which is given 1-2 times/day for 7 days. The results of the treatment showed healing, with the head, comb, and wattle appearing to be clean from white scales.